SOSIALISASI ASPEK KESELAMATAN PADA INSTALASI LISTRIK - Desryanto, Nurhedhi; Widiarto, Hendro; Koswara, Iwan; Putra, Adli Adia; Isdy, Muhammad Zaky; Soebiantoro, Rubby; Taryana, Taryana; Kosasih, Ahmad (Universitas Pahlawan Tuanku Tambusai, 2024)
Pengabdian Kepada Masyarakat (PKM) dengan judul